Economic values of natural resources along Tehran-Shomal Freeway, Iran - Hejazi, Rokhshad (2012)
Tehran-Shomal freeway was constructed to have a safer and shorter travel route. However it causes degradation of valuable natural resources along the constructed freeway. There is a paradox between a safer route and natural resource degradation. The traffic accidents are the second factor for Iranian death. There are 235 million thousands of fatal traffic accidents in Iran. There is a serious need for a safer and shorter travel route between Iranian people. On the other hand, Iran forest area is very poor. There are many concerns about very valuable and fragile natural resources along Tehran-Shomal freeway. We attempt to estimate the economic values of natural resources along Tehran-Shomal freeway in this study. First specific objective is to investigate community awareness and attitudes towards supporting the natural resources. Second specific objective is to determine effect of socio-economic characteristics of the community on willingness to pay (WTP). Third specific objective is to estimate the willingness to pay (WTP) of the natural resources conservation along the Tehran-Shomal freeway. The last specific objective is to determine the benefits and costs of the Tehran-Shomal freeway construction. The contingent valuation method (CVM) was used to estimate the economic values of the natural resources along the Tehran-Shomal freeway. It is only approach accessible for estimation non-use values. We also applied close-ended CVM survey. The format of the close ended was a dichotomous choice (DC) question. Respondents give a "Yes" or "No" answer to wheatear or not they would pay. Our results indicated that the community has sufficient awareness about environmental issues such as endangered species or natural resources conservation. They had adequate attitude about the natural resources along Tehran-Shomal freeway. For example, 62% of individuals manifested varying levels of worriment about the natural resources along the freeway. Gender, environmental sensitiveness, education and income variables are all significant explanatory variables in the WTP model. The cost-benefit analysis (CBA) suggested that the benefits of the Tehran- Shomal freeway construction are more than its costs. The estimated mean WTP was US$1.84. The total WTP of supporting natural resources along Tehran-Shomal freeway was estimated at US$77 million per year which is about 0.23% of Iranian GDP. The individuals were generally willing to pay up to 4% of their income for conservation of natural resources along the Tehran-Shomal freeway. Tehran-Shomal freeway has been started sixteen years ago but has not completed yet,because its benefits had been never estimated. We make sure policy makers for completion the Tehran-Shomal freeway construction. According our results most of people were concern for natural resources in part one and three of the Tehran-Shomal freeway. Policy makers can continue construction operations in the part two and three of the freeway. We recommend environmental management plan (EMP) reexamined in the part one and four which have more valuable natural resources.